Current and Proposed Non-Oil Tax System in Azerbaijan. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
This paper analyzes developments in non-oil tax policy, administration, and revenues in Azerbaijan, and suggests measures for further improvement. The main finding is that Azerbaijan's non-oil tax revenues increased significantly as a share of non-oil GDP in the last five years, but remain below potential. The non-oil tax revenue shortfall is mainly due to widespread exemptions, but there is scope for strengthening tax and customs administration. In the short term, expanding the tax base and better tax and customs administration will yield more revenues. In the medium term, more far-reaching reforms including reducing some direct tax rates, should be considered. The overall reform package could be made broadly revenue neutral by improving taxpayers' compliance and reducing exemptions.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet